The implementation of corporate social responsibilities (CSR) among G7 contractors in Malaysia / Hamimah Adnan ...[et al.] - Adnan, Hamimah; Mohd Zahir, Mas Elida; Wan Ismail, Wan Norizan; Rosman, Muhammad Redza (Faculty of Architecture, Planning and Surveying Universiti Teknologi MARA, Shah Alam, 2019)
Corporate Social Responsibility (CSR) is one of way to encourage among the stakeholders to improve not only the society, but environment and economy of affected people. This paper aims to identify the implementation, challenges and ways to enhance Corporate Social Responsibility (CSR) among G7 Contractors registered under the Malaysian Construction Industry Development Board. (CIDB in Malaysia. Quantitative and qualitative methodology were involved which involved questionnaires survey and interviews. Questionnaires were distributed to 150 respondents with 32 replied and 5 interviews were held among the respondents. The findings show that the highest level of CSR implementation is in the relationship with clients and suppliers. Most respondents agreed that the biggest challenges in implementing CSR were lack of support from top management and lack of time. It also showed that most respondents agreed that the ways to enhance the implementation of CSR were the involvement of system of governance transparency with investors and shareholders, application of policy by employees, close relationship with the clients and suppliers, concrete actions towards community and adoption of measures on the environmental impact. It is recommended for the implementation of CSR and ways to overcome the challenges needed to be enhanced to reach the highest level of implementation and every stakeholder needs to act for effective improvement to enhance the implementation.